Detrital zircon provenance from the Neuquén Basin (south-central Andes): Cretaceous geodynamic evolution and sedimentary response in a retroarc-foreland basin - Di Giulio, A. (2012)
The surface response, in terms of drainage pattern changes, to the Cretaceous geodynamic reorganization of the Andean subduction zone between 36°S and 41°S is reconstructed through the geochronology-based provenance study of alluvial detrital zircons. The age spectra obtained by 500 spot U-Pb ages record an eastward provenance of detritus coming from the foreland during the Early Cretaceous backarc extensional stage, followed by westwardsourced clastics coming from the Cordillera during the Cenomanian. This drainage pattern reversal fits the regional unconformity in the sedimentary record that is linked to the geodynamic reorganization of the continental margin from an extensional to a compressional regime, forcing the Neuquén Basin to evolve from a retroarc to a foreland stage. After this inversion, the clastic systems progressively returned to be mainly fed by the foreland, due to the uplift of the peripheral bulge as a consequence of the Late Cretaceous thrust front migration. This tectonic evolution of the Neuquén Basin and the related response of the drainage pattern are thought to be the surface expression of the dip decrease of the Benioff subduction zone.